Use of Survey and Delphi Process to Understand Trauma Anesthesia Care Practices. (May 2018) - Kuza, Catherine M.; Vavilala, Monica S.; Speck, Rebecca M.; Dutton, Richard P.; McCunn, Maureen
Abstract : BACKGROUND: Few trauma guidelines evaluate and recommend anesthesiology practices and there are no trauma anesthesia-specific guidelines. There is no information on how anesthesiologists perceive clinical practice patterns. Our objective was to understand the perceptions of anesthesiologists regarding trauma anesthesia practices. METHODS: A survey assessing anesthesia management of trauma patients was distributed to 21, 491 anesthesiologists. A subset of 10 of these questions was subsequently reviewed by a trauma anesthesiology focus group through a 3-round web-based Delphi process. A question was deemed to have respondent consensus if the response with the highest percentage of agreement was unchanged between rounds 1 and 2. RESULTS: A total of 2360 anesthesiologists (11% response rate) responded to the survey. Results demonstrated that the practitioners' answers conflicted with existing surgical trauma society recommendations (ie, when to transfuse component therapy), and several areas that lacked any guidelines, resulted in response variability among anesthesiologists where not 1 answer achieved >75% agreement (ie, intubation technique of choice for patients with uncleared cervical spine). Thirteen trauma anesthesiologists participated in round 1 (response rate 100%), and 12 responded in rounds 2 and 3 (response rate 92%) of the Delphi process. None of the questions received 100% agreement. Consensus was achieved on 9 of 10 statements pertaining to trauma anesthesia care. Consensus was not reached on the intubating technique in a hemodynamically unstable patient with an uncleared cervical spine with deficits. Delphi participant opinion conflicted with existing guidelines on 2 statements: the use of cricoid pressure, and when to begin blood component therapy. CONCLUSIONS: There are several important areas of trauma anesthesia practice where guidelines do not exist and several where existing guidelines are not endorsed by the majority of practitioners who completed our survey. The lack of consensus on trauma anesthesia management and the variation in survey responses demonstrate a need to develop evidence-based trauma anesthesia guidelines.